PUEBI Error Analysis on Instagram Account Posts @bank_indonesia_sumut - Sipangkar, Cici Paranita; Sibarani, Melly Monica; Sembiring, Serina Br; Tarigan, Sovia Loren Br; Simarmata, Vernalia Sonya Kristina (Lembaga Riset Mutiara Akbar, 2024)
This study aims to analyze the errors in the use of the General Guidelines for Indonesian Spelling (PUEBI) in the posts of the Instagram account @bank_indonesia_sumut. In the digital era, social media has become an effective communication tool, including for government agencies such as Bank Indonesia. However, errors in the use of spelling can affect the image of professionalism and the credibility of the information conveyed. This study uses a qualitative descriptive method by collecting data in the form of randomly selected Instagram posts. The results of the analysis show several common errors, such as capitalization, punctuation, and the use of standard words. These findings are expected to be used as evaluation material to improve the quality of the use of Indonesian in accordance with the PUEBI rules on social media.